2008
DOI: 10.1038/bmt.2008.397
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of the allo-immune response in multiple myeloma: where do we go from here?

Abstract: AlloSCT is a potentially curative procedure for haematological malignancies and marrow failure syndromes. However, unlike leukaemia and lymphoproliferative disorders, AlloSCT has yet to find its place in the clinical management of patients with multiple myeloma. AlloSCT in multiple myeloma is associated with a high procedurerelated mortality (TRM up to 35%) when full-intensity conditioning is used and only up to 36% of cases show long-term disease-free survival. The introduction of reduced intensity conditioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In myeloma, a malignancy of mature B-cells, both dysfunctional effector responses and augmented regulatory cell compartments have been described [1,10,[29][30][31]. To date, attempts to overcome this have been largely limited to the adoptive immunotherapeutic effect of an allogeneic stem cell transplant, which though effective, entails inherent procedure-related toxicity which limits its suitability for the majority of myeloma patients [32]. As such, an alternative immunotherapeutic strategy is required and thus a re-examination of the defined immune defects is warranted.…”
Section: Discussionmentioning
confidence: 97%
“…In myeloma, a malignancy of mature B-cells, both dysfunctional effector responses and augmented regulatory cell compartments have been described [1,10,[29][30][31]. To date, attempts to overcome this have been largely limited to the adoptive immunotherapeutic effect of an allogeneic stem cell transplant, which though effective, entails inherent procedure-related toxicity which limits its suitability for the majority of myeloma patients [32]. As such, an alternative immunotherapeutic strategy is required and thus a re-examination of the defined immune defects is warranted.…”
Section: Discussionmentioning
confidence: 97%
“…With the current data, Allo-RIC from either related or unrelated donors seems the most promising allogeneic approach, but there may still be a role for myeloablative allografting in selected patients (ie, younger patients with poor cytogenetics). 101 Who are the patients most likely to benefit from Allo-RIC?…”
Section: Unsolved Questions In Allogeneic Transplantationmentioning
confidence: 99%
“…14,15,16 Allogenic transplantation (allo-SCT) has been performed in a small proportion of patients throughout this period but the potential benefits were marred by regimen-related toxicity and graft-versus-host disease in the pursuit of the putative graft-versus-myeloma effect. 17,18 However a limited number of studies have now been reported showing that the benefits of allo-SCT may be obtained by combining a reduced-intensity allo-SCT with a prior ASCT (auto-allo) thus reducing the transplant-related mortality, although benefit for the auto-allo group only became obvious after five-year followup. 18,19 It is of interest that only now are we closer to harnessing a targeted immunotherapy-based therapeutic strategy in myeloma with the evolution of CAR T-cells and bi-specific T-cell engager (BiTE) technology in MM.…”
Section: Therapeuticsmentioning
confidence: 99%